Role of endothelial cells and angiotensin converting enzyme-II in COVID-19 and brain damages post-infection - Mehboob, Riffat; von Kries, Jens Peter; Ehsan, Kashifa; Almansouri, Majid; Bamaga, Ahmed K. (Frontiers in Neurology, 2023)
Severe acute respiratory syndrome corona virus 2 (SARS CoV-2) causes Corona virus disease 2019 (COVID-19) which became a pandemic in late 2019 and early 2020. Apart from many other symptoms of this infection such as loss of smell and taste, rashes, body aches, fatigue, psychological and cardiac symptoms, it also causes vasodilation in response to inflammation via nitric oxide release. SARS CoV-2 affects the microcirculation resulting in the swelling of endothelial cells and damage, micro thrombosis, constriction of capillaries and pericytes damage that are vital for the integrity of capillaries, angiogenesis and healing process. Cytokine storming has been associated with COVID-19 illness. Capillary damage and congestion may cause limited diffusion exchange of oxygen in lungs and hence hypoxemia and tissue hypoxia occur. This perspective will explore the involvement of capillary damage and inflammation to the persistent symptoms and severity of COVID-19 by their interference with blood and tissue oxygenation as well as brain function. Overall effects of the capillary damage due to COVID-19, microvascular damages and hypoxia in vital organs are also discussed in this perspective. This vicious cycle once initiated, causes inflammation due to hypoxia resulting in limited capillary function, which in turn causes inflammation and tissue damage. Low oxygen levels and high cytokines in brain tissue may lead to brain damages. The after effects may be in the form of psychological symptoms such as mood changes, anxiety, depression and many others that need to be investigated